The term structure of country risk and valuation in emerging markets - Cruces, Juan José (2002)
Most practitioners add the country risk to the discount rate when valuing projects in Emerging Markets. In addition to the problems already pointed out in the literature, in this paper we claim that such practice leads to a pro-cyclical bias in the valuation of long-term projects. The mismatch between the duration of the project and the duration of the most widely used measure of country risk, J. P. Morgan's EMBI, leads to an overvaluation of long-term projects in good times (upward sloping default risk) and to an undervaluation of them when short-term default risk is high (the contrary is true with respect to short-term projects.) Using sovereign bond data from five Emerging Markets, we estimate a simple model that captures most of the variation of default probabilities at different horizons for a given country at one point in time. This model can be used to solve the misestimation problem.